Optimization Of Retaining Wall And Building Foundation Design For The People's School In Jeulikat Village, Blang Mangat District, Lhokseumawe City - arissasabilla; Nanik Handayani; Neneng Ipak Mardiah Bukit; Marini Bravikawati (Program Studi Teknik Sipil, Fakultas Teknik. Universitas Samudra, 2026)
The construction of the People's School Building in Jeulikat Village, Blang Mangat District, Lhokseumawe City, Aceh Province is one of the government's strategic programs to improve educational facilities. The site conditions consist of uneven topography and clayey sand soil requiring proper retaining wall and foundation design. This study aims to optimize retaining wall and foundation systems based on soil parameters, structural loading, and Indonesian geotechnical standards. A quantitative analytical method was employed using soil investigation data, laboratory testing, and calculations based on Rankine Earth Pressure Theory, Terzaghi Bearing Capacity Theory, Meyerhof Method, and Indonesian National Standards. The results indicate that a cantilever retaining wall with a height of 4 meters provides safety factors against sliding, overturning, and bearing capacity of 2.15, 2.48, and 3.12 respectively, satisfying engineering requirements. Furthermore, a spread footing foundation measuring 2.0 × 2.0 meters provides an ultimate bearing capacity of 845.36 kN with a safety factor of 3. The optimized design reduces concrete consumption by approximately 12.4% compared with conventional designs while maintaining structural safety